The structure of subpopulations of stallion spermatozoa after thawing differs between good and poor freezers - Filipa Bubeníčková; Jiří Šichtař; Linda Nováčková; Jitka Sirohi; Ondřej Šimoník (Czech Journal of Animal Science, 2020)
The aim of this study was to evaluate differences in the presence of sperm subpopulations in frozen-thawed semen in stallions with different freezability. The motility of individual spermatozoa of 24 stallions from 15 breeds was evaluated using computer-assisted sperm analysis (CASA) immediately after thawing (T0) and after 30 min of incubation (T30). In accordance with our previous studies, samples were initially divided based on their total motility into categories of good (GF) and poor (PF) freezers. K-means cluster analysis of kinematic parameters of spermatozoa was used to divide motile sperm (n = 57 630) into three subpopulations. Analysis of variance was used to evaluate differences in the subpopulations between GF and PF stallions at the times of incubation T0 and T30. Statistically significant differences were found in most kinematic parameters between PF and GF stallions as well as between the times of incubation T0 and T30 (P < 0.05). Spermatozoa of good freezers are represented more frequently in the fast and medium fast subpopulations and are faster and more linear than those of poor freezers (P < 0.05). Sperm from PF stallions were more strongly affected by longer incubation. The percentage of sperm in the fast and medium fast subpopulations was lower in samples from PF stallions, but assessment of the motility parameters in particular sperm subpopulations revealed that these sperm had good velocity. Poor freezer samples had lower sperm quality due to a reduced total proportion of motile sperm, and these samples were more sensitive to prolonged time after thawing. Thus, an efficient sperm selection method or a special insemination technique should be used for obtaining doses from stallions with poor freezability. Our study showed that the CASA system and cluster analysis are promising tools for better understanding the significant differences in the individual stallion freezability, and further research should be focused on their application in the field.